Novel semi-fluorinated poly(ether imide)s with benzyl ether side groups: Synthesis, physicochemical characterization, gas transport properties and simulation. (15th July 2020) - Chatterjee, Rimpa; Ganesh Kumar, Anaparthi; Nikiforov, Roman; Ryzhikh, Victoria; Belov, Nikolay; Padmanabhan, Venkat; Yampolskii, Yuri; Banerjee, Susanta
Graphical abstract: Highlights: New poly (ether imide)s with benzyl ether and -CF3 groups have been prepared and characterized. The polymers exhibited good film forming ability and excellent thermal and mechanical stability and low dielectric constant. Gas transport parameters have been estimated using three independent methods. The group contribution method predicts the permeability coefficients exceptionally well with the experimental P values. The molecular dynamics simulation shows a similar trend but a somewhat lesser agreement with the experimental P values. Abstract: The present work reports the preparation of several new poly(ether imide)s (PEIs) from the benzyl ether substituted, fluorinated diamine monomer, 4, 4 ′ -((2 ′, 5 ′ -bis(benzyloxy)-3, 3 ′' -bis(trifluoromethyl)-[1, 1 ′ :4, 4 ′' -terphenyl]-4, 4 ′' -diyl)bis(oxy))dianiline (TADBE) with different fluorinated and non-fluorinated aromatic dianhydrides as the materials for membrane-based gas separation applications. The PEIs were readily dissolved in numerous organic solvents and cast into freestanding flexible films with tensile strength up to 159 MPa and elongation at break up to 106%. The films were optically transparent and showed dielectric constant as low as 2.47 at 1 MHz and 30 °C for the polymer derived from 6FDA (PEI-b). The structural elucidation of the polymers was done by 1 H NMR and FTIR studies. The weight average molecular weight of the polymers was as high as about 255000 g/mol, and dispersity values were with the range as expected for condensation polymers (2.1–2.8). The thermal stability of PEIs was tested carefully to judge their ability for membrane-based application. The polymers showed 10% weight loss temperature above 440 °C in the air with high Tg values (as high as 252 °C) under nitrogen. Three independent methods were used to estimated the gas permeability coefficients of the PEIs. The structure-property correlations on gas transport properties and chemical structure and different physical properties of these PIEs were established. The best combination of selectivity and gas permeability (P) value is seen for the polymer with 6FDA fragment (PEI-b). The group contribution method predicts the permeability coefficients exceptionally well in all three PEIs and for different gases. Molecular dynamics provides a better insight on free volume, free volume size distribution, and morphology of the PEIs.